O desenvolvimento da afetividade nas práticas pedagógicas na Educação Infantil à luz da Teoria Histórico-Cultural - Tessarin, Maira Juliana (Universidade Federal de São Carlos, 2023)
This research was carried out within the Center for Studies, Research and Extension on the School of Vigotsky (NEEVY). Based on the Historical-Cultural Theory, especially on Vygotsky's texts, we find the concept of emotions as a fundamental element for the learning of human beings. This is because, upon entering school, children are affected by feelings and emotions that influence their perception of relationships and the world around them. Consequently, such social learning situations are challenging for them and for the teachers' actions. Thus, this investigation proposed to expand the analyzes of research already carried out regarding the development of affection with children, in Early Childhood Education. That said, our research question intended to answer the following question: what are the main contributions and foundations found in current research subsidized by the Historical-Cultural Theory, for the development of affectivity in children in Early Childhood Education? Therefore, our objective was to deepen the theoretical-practical discussion regarding the pedagogical work for the development of affectivity in children in Early Childhood Education, based on the research already carried out in the Cultural Historical Theory. As a methodology, we carried out a bibliographical and theoretical research, based on the method of historical-dialectical materialism and the genetic method of the Historical-Cultural Theory, based on the procedures and instruments proposed by Salvador. From the applied descriptors and filters, we found 2,719 national and international articles, of which 17 referred to our object of study. Data analysis occurred through three guidelines. In the first, we address the characteristics of research on affectivity in Brazil and in the world; in the second, we relate the main concepts of the Historical-Cultural Theory for the development of affectivity and in the third guideline, we discuss the subsidies that contribute to the pedagogical practices. As a result, we obtained research carried out in all continents that demonstrated the overwhelming fact of the need to modify attitudes towards more affective relationships. We affirm through the results that the dichotomization between reason and emotion, affection and cognition are convenient to the political and economic context of the current capitalist society, and we have in the dialectic conception an essential instrument to seek this overcoming. As subsidies for teaching practices, we suggest that pedagogical practices focused on analyzing the quality of children's expressive signals. Thus, encouraging participation, cooperation, sharing, communication appropriate to the activity, games and games are important ways for the development of affectivity. On the other hand, repressions, punishments and fanciful lies have negative effects, as they crystallize negative emotional experiences. Another excellent tool is the use of Art and the child's imagination in pedagogical practices, with its use in the plastic arts, poetry, music, dramatization and role-playing, since this connection unites emotion, interaction, creation and fantasy in the same activity, in addition to enabling emotional anticipation. Another important result of the research is the advancement of the Historical-Cultural Theory in research in Brazil and in the world, as its theoretical assumptions, method, methodology and concepts make it an important theoretical reference to explain the need for affectivity in social relations.
Affection development in pedagogical practices in Early Education in the light of Historical-Cultural Theory
Keywords: Afetividade; Emoções; Sentimentos; Teoria Histórico-Cultural; Vigotsky; Educação infantil; Affectivity; Emotions; Feelings; Cultural-Historical Theory; Early education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO